(3eNJUQ aj GdCOhjI GdeQcHIs - (3eMeO Hf HgQGe Hf eMeO GdbdGfSj GdSeQbfOj, HOQGdOjf , J (B590 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdHGQY GdbdGfSi (B: (3GdMeO ddg GdMcje GdbGgQ GdYRjR GdYGdi abO OYGfi Edi LejY gPG GdeNJUQ Cfi QCjJ QLd GdbQGHGPjfGJ eTMhfI ef fSN GdCOhjI GdeQcHI GdJi HfOQ hbhY GdMGLI EdjgG s
(3BNQgG (B:s
(3bGd CHh YHjO Gddg Hf LHQGFjd ai efJNHGJg ef WHGFY GdMjhGf hNhGUgG (B: (3bO LQHJ gPG aUM hJYdd GdScQ s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3cJHJ HYV GdcdeGJ HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs